Assertive foreign policy despite diminished capabilities: Russian involvement in Syria. Issue 3 (26th May 2020) - Moulioukova, Dina; Kanet, Roger E.
ABSTRACT: In 2015, more than 60 per cent of Russians supported the actions of their government in Syria, despite the lack of clarity on the reasons behind Moscow's involvement. One would expect such a bold move to come from a powerful state with a healthy economy and strong geopolitical leverage. However, in 2015, Russia was struggling economically; its inflation had been rising and the GDP had contracted dramatically. The Kremlin's decision to engage in Syria further strained the country's already tense relations with the West. In this article, we argue that in some instances traditional security studies do not provide sufficient tools to understand some of the choices that Russia makes in its foreign policy. While physical security contingent on the state's ability to project power is important to the Kremlin, in many cases, national interest in the preservation of the continuity of what is called ontological security (a security of being) prevails.